Labor Redemption in Work Law - Elmore, Andrew (2020)
People with criminal records must find and keep work to reintegrate into society. But private employers often categorically exclude candidates with criminal record histories, especially if the candidate is African American or Latinx. The conventional wisdom is that workplace laws offer little to address this problem. People with criminal records are not a protected class under Title VII, and many employers fear that hiring people with criminal records invites negligent hiring liability. Ban the Box privacy laws delay but may not deter overbroad criminal background checks. This Article challenges this standard account by shifting focus to the state in imposing arbitrary barriers to work. I expose a dignity interest in the removal of these unnecessary barriers, or “labor redemption.” I find foundations of labor redemption in successful constitutional challenges to denials of public employment and occupational licenses. Labor redemption is also, increasingly, a statutory right, in the automated sealing and expungement of old and minor criminal records, and issuance of state certifications of individuals as rehabilitated. Reconceiving of these criminal justice reforms as work law protections can resolve structural limitations to Title VII and Ban the Box laws by providing evidence of rehabilitation, and permit courts to balance the redemption and security interests in negligent hiring claims. Labor redemption also offers a law reform approach to facilitate reintegration through work without imposing new legal obligations on private employers, or requiring an extension of existing employment laws. This Article’s assessment offers lessons for other areas in which private decision makers exclude candidates because of state-imposed stigmas, especially the close analogy of housing discrimination